Teen Out-of-Wedlock Births and Welfare Receipt: The Role of Childhood Events and Economic Circumstances - An, Chong-Bum; Haveman, Robert; Wolfe, Barbara (The Review of Economics and Statistics, 1993)
Using 20 years of longitudinal data on nearly 900 girls aged 0 to 6 in 1968 (19 to 25 in 1987) from the University of Michigans Panel Study of Income Dynamics the authors measure the influence of family background individual characteristics economic resources (or the lack thereof) and the experience of particular disruptive family events on the probability that a teenager will give birth out of wedlock and subsequently apply for and receive welfare....Among the many findings of the investigators is that teenage daughters whose mothers have more education are less likely to give birth out of wedlock that teens whose mothers received welfare are more likely to give birth out of wedlock and receive welfare themselves and that teens who grew up in a home experiencing stressful events (e.g. parental separation geographic moves) are more likely to give birth out of wedlock. (EXCERPT)